Long‐term risk of colorectal cancer after screen‐detected adenoma: Experiences from a Danish gFOBT‐positive screening cohort. Issue 4 (25th January 2020) - Bjerrum, Andreas; Lindebjerg, Jan; Andersen, Ole; Fischer, Anders; Lynge, Elsebeth
Abstract : Fecal occult blood test (FOBT) screening for colorectal cancer (CRC) is implemented in several countries. Approximately half of all FOBT‐positive persons have screen‐detected adenomas. Despite removal of these, patients with large/multiple adenomas have increased risk of later developing new advanced adenomas and CRC. International guidelines exist for colonoscopic surveillance following adenoma removal. These divide patients into low‐, intermediate‐ and high‐risk groups. We followed 711 FOBT‐positive patients with screening adenoma identified during population‐based CRC screening in two Danish counties in 2005–2006. As reference population, we included 1, 240, 348 persons in the same age group from the rest of Denmark not included in the screening. We estimated the long‐term CRC risk stratified by adenoma findings during screening and compared to the reference group. After 12 years follow‐up, the CRC incidence among all adenoma patients was 322 cases per 100, 000 person‐years (95% confidence interval [CI]: 212–489) ranging from 251 (95% CI: 94–671) to 542 (95% CI: 300–978) cases per 100, 000 person‐years in the low‐ and high‐risk groups, respectively. In the reference population, the CRC incidence was 244 (95% CI: 242–247) per 100, 000. Patients with screen‐detected high‐risk adenomas after a positive FOBT had an almost doubled risk of CRC compared to the reference population (adjusted hazard ratio [aHR] 1.95, 95% CI: 1.08–3.51), and the incidence in those with no follow‐up visits was over 3.6 (aHR 3.64, 95% CI: 1.82–7.29) times the incidence in the reference population. The increased CRC risk could be controlled if high‐risk patients underwent follow‐up colonoscopy (aHR 0.87, 95% CI: 0.28–2.69). Abstract : What's new? About half of individuals who have a positive fecal occult blood test (FOBT) will have one or more adenomas, potentially increasing their risk of later developing colorectal cancer (CRC). While surveillance is recommended to detect and remove these precursor lesions, evidence of surveillance effectiveness on CRC incidence is scarce. This study shows that in persons with high‐risk adenomas detected following positive FOBT screening, long‐term risk of CRC is nearly doubled, relative to the general population. This risk could be controlled, however, if high‐risk patients were identified via European guidelines for CRC screening and diagnosis and underwent follow‐up colonoscopic surveillance.